Statistics on bankruptcy of companies in Poland - Tomczak, Sebastian Klaudiusz (Management Sciences, 2018)
The phenomenon of business failure in Poland came into being anew with the fall of the communist rule – it was the beginning of the 1990s, and the transition period from a centrally controlled market to a market economy was triggered. At that moment the market was a place where verification was being made regarding whether or not companies would be able to function, and consequently should they file for bankruptcy? Bankruptcy can be called a controlling device designed to eliminate the weakest links from the market, leaving the strongest players. This led to the creation of new statistical data, access to which has become easier over the years. This paper presents selected statistical data on bankruptcies of enterprises in Poland in the period 1990-2017. These data are presented by various credit information agencies by sector and region. However, these figures involve no relationship between the number of bankrupt enterprises and the number of operating ones. For this reason, the author calculated the statistical data, taking into account the relevant facts. The paper also introduces the business insolvency index and the newly established business index. The author suggested analyzing both of them in the analysis of bankruptcy data
Management Sciences, 2018, vol. 23, no. 3, s. 39-50
Keywords: bankruptcy; statistics; business; business insolvency index; upadłość; dane statystyczne; przedsiębiorstwo; wskaźnik niewypłacalności przedsiębiorstw